URGENSI PEMBATASAN PARTAI POLITIK PADA SISTEM PEMERINTAHAN PRESIDENSIAL DI INDONESIA - Allicia Putri Prasetyaji; Ahmad Sholikhin Ruslie (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The constitutional government system chosen by the Indonesian people is a presidential government system, a government which in practice is often encountered with practices that lead to a parliamentary government system. The Confusion System, which therefore influences the presidential election, will not be able to regulate an independent cabinet because it must prepare the interests of political parties to avoid conflicts with the House of Representatives (DPR). Such practice is certainly not healthy in implementing a presidential system because it will divert government approval to carry out its function as an executive institution. The urgency of limiting political parties in a presidential system is for government stability, because theoretically in a presidential government system the effectiveness of the number of political parties is one to two parties because this government system adheres to a simple party system